Comparative proportionality review: A nationwide examination of reversed death sentences - Wallace, Donald H. (American journal of criminal justice, 1997)
A required part of the appellate review of death sentences in many capital punishment jurisdictions is comparative proportionality review. This procedure requires the court to compare the death sentence under review with sentences in similar cases to determine whether it is excessive. This article examines those death sentences from across the country that have been reversed on comparative proportionality grounds. Relatively few death sentences have been reversed on these grounds, and the number of reversals is decreasing. The reviews that reverse sentences infrequently compare only to other death sentences, commonly use a method that requires more than a mere common aggravating factor for selecting comparison cases, and rarely use the frequency method of comparative proportionality review.